Synthesis and evaluation of fluorous polycyclic aromatic hydrocarbon derivatives for organic electronics - Rippy, Kerry C., author; Strauss, Steven H., advisor; Prieto, Amy L., committee member; Sites, James R., committee member; Szamel, Grzegorz, committee member (Colorado State University. Libraries, 2019)
Advances in the performance of electron acceptor materials for organic electronics critically depend on the efficiency of synthetic routes for new materials and fundamental understanding of the correlation between molecular structure and electronic and solid-state properties. The research presented here endeavors to address both of these needs, by developing original methods for synthesis of new organic electron acceptor materials, and by characterizing relevant properties of the resulting materials. In total, synthesis and analysis of more than 60 new molecules is presented in this work. These molecules are derivatives of polycyclic aromatic hydrocarbons (PAHs) and hetero-PAHs functionalized with fluorous moieties, synthesized via development of substrate-specific efficient, single-step direct-substitution methods. Investigation of solid-state and electronic properties focused upon effects of structural motifs including (i) the type, number, and position of electron withdrawing fluorous substituents (ii) the size and shape of aromatic π systems, and (iii) presence of hetero atoms within the aromatic core. The first chapter of this work details the development and optimization of a gas-phase radical reaction between the perfluoroalkyl diiodide 1,4-C4F8I2 and the PAH triphenylene (TRPH). The perfluoroalkyl diiodide, with two C–I bonds, one at either end, has the unique ability to bind to vicinal C atoms, forming a 6-membered ring. A family of TRPH derivatives functionalized with such rings was synthesized, and the reaction was optimized. Additionally, reductive partial defluorination of the perfluoroalkyl ring was achieved, leading to aromatization of the fluorous substituent (RD/A). The extension of the π-system, as well as the effect of fluorine atoms bound directly to the aromatic system, was examined with respect to solid-state packing and electronic levels. In Chapter 2, results of screening of 13 new PAH and n-hetero PAH substrates with respect to their reactivity towards 1,4-C4F8I2 are described. Pure compounds derived from these reactions are presented, adding several new families to the library of fluorous PAH derivatives. Unique reactivities and interesting potential applications are discussed for several of these families. Solid-state packing and electronic properties are analyzed for selected derivatives. A particularly promising family of fluorous acceptors is presented and analyzed in greater depth in Chapter 3. It is based on the substrate phenazine (PHNZ). This family of molecules is notable because several derivatives exhibit enhanced acceptor strength and linearly-fused molecular structures resembling the acene class of PAHs, a high performing class of materials widely used in organic electronics. Results suggest that the molecules investigated in this chapter would be suitable for applications as air-stable n-type semiconductors in electronic devices. Finally, in Chapter 4, the characterization of a family of trifluromethylated acridine (ACRD) derivates is described. This investigation yields new insights into the reactivity of ACRD. Furthermore, detailed structural, spectroscopic and electronic property analysis combined with computational data revealed that not only the number of substituents, but also the position of substituents affects electronic energy levels. This finding not only expands basic understanding of how molecular structure affects electronic properties of PAHs, but also provides a valuable new tool for molecular design of acceptors with desirable properties.
Keywords: electrochemistry; fluoroalkylation; polycyclic aromatic hydrocarbons (PAHS); electron acceptors; aromatization; n-type organic semiconductors